Economic reforms, technological intensity and industrial development in India - Mehta, Swati (2011)
The impact of the 1991 reforms on the Indian manufacturing sector has been a subject of much debate. The reforms were expected to result in a high growth are coupled with a structural change towards high technology industries. This paper analyses data on 60 three-digit industries, reclassified into four technology-intensive subgroups, for the period 1980-81 to 2005-06. Dividing this period into the pre-reform (1980-81 to 1991-92) and the post-reform (1992-93 to 2005-06), the paper uses the single kinked model to reveal a slower trend growth rate of value added for about 77% of the industries in the post-reform period. Further, the study does not find any significant structural transformations within the organised manufacturing sector, which is still dominated by relatively low technology industries. The results thus refute the neo-liberal optimism regarding reforms. In an increasingly technology-driven world, promoting industrialisation is a multidimensional complex task that requires a constructive role of the government. - Reproduced.
Keywords: Industrial development - India.Technology - India; Economic reform - India; Economic reform